Transformasi Peran Guru Sekolah Dasar pada Pembelajaran Abad 21 - Basuki, Sigit Rahmat; Hidayah, Ratna (Social, Humanities, and Educational Studies (SHES): Conference Series, 2025)
The rapid advancement of technology and social change in the 21st century has demanded a major transformation in the role of primary school teachers—from traditional instructors to active, adaptive, and innovative facilitators. This article aims to explore how the transformation of teacher roles supports the development of students’ 21st-century skills and what competencies are needed to meet modern educational challenges. The method used is a literature review with a qualitative descriptive approach based on ten relevant scholarly articles. The findings emphasize three main aspects: (1) shifting from teacher-centered to student-centered learning, (2) strengthening digital literacy and integrating learning technologies, and (3) applying project- and problem-based approaches to develop 4C skills. This study recommends continuous training, an innovative school culture, and supporting infrastructure to enable teachers to perform their roles effectively in the digital era.Perkembangan teknologi dan perubahan sosial pada abad ke-21 menuntut transformasi signifikan dalam peran guru sekolah dasar, dari pengajar tradisional menjadi fasilitator pembelajaran yang aktif, adaptif, dan inovatif. Artikel ini bertujuan mengkaji bagaimana transformasi peran guru sekolah dasar dapat mendukung pengembangan keterampilan abad ke-21 siswa, serta kompetensi apa saja yang dibutuhkan guru dalam menghadapi tantangan pendidikan modern. Metode yang digunakan adalah kajian literatur dengan pendekatan deskriptif kualitatif terhadap sepuluh artikel ilmiah relevan. Hasil kajian menunjukkan bahwa transformasi peran guru mencakup tiga fokus utama: (1) perubahan dari teacher-centered menjadi student-centered learning, (2) penguatan literasi digital dan integrasi teknologi pembelajaran, serta (3) penerapan pendekatan berbasis proyek dan masalah untuk pengembangan keterampilan 4C. Penelitian ini merekomendasikan perlunya pelatihan berkelanjutan, budaya inovatif di sekolah, serta infrastruktur pendukung agar guru mampu menjalankan perannya secara optimal di era digital.